Latent stability and change in subgroups of social anxiety and depressive symptoms in adolescence: a latent profile and transitional analysis - Magson,NR; Van,Zalk N; Mörtberg,E; Chard,I; Tillfors,M; Rapee,RM (Journal of Anxiety Disorders, 2022)
BackgroundSocial anxiety and depressive symptoms increase markedly during adolescence. Most research examining the emergence of these symptoms has used a variable-centered approach providing little information about how these symptoms group together in individuals over time.MethodA person-centered approach utilizing latent profile and latent transitional analyses was applied to a large adolescent sample (N = 2742, Mage=13.65; SD=0.63; 47.9% girls). Subgroups differing in their expressions of social anxiety and depressive symptoms at each of four annual time points were identified and then change in membership of these groups was evaluated.ResultsFour subgroups were identified: 1. Low Distress, 2. Socially Anxious, 3. Dysphoric, and 4. Comorbid. The low distress group was the largest and most stable, followed by the socially anxious group, who most commonly transitioned into the comorbid group. In contrast, the dysphoric group were most likely to remit and move to the low distress group. The comorbid group was the smallest and least stable, although once in this group, three quarters of adolescents remained in this group over time.ConclusionEarly intervention is particularly imperative for socially anxious adolescents with or without comorbid depressive symptoms as they are the least likely to improve across the adolescent years.